Clinical characteristics and risk factors for perinatal arterial ischemic and hemorrhagic stroke: a comparative study - Liu, Chongchong; Zhang, Yi; Yang, Run; Xia, Shiwen (Frontiers in Pediatrics, 2025)
BackgroundPerinatal cerebral infarction (PCI) is a common cause of neurological complications in neonates. This study aimed to compare the clinical characteristics and risk factors of perinatal arterial ischemic stroke (PAIS) and perinatal hemorrhagic stroke (PHS) to inform early recognition and intervention strategies.MethodsWe conducted a retrospective analysis of 124 neonates diagnosed with PCI, admitted to the neonatal intensive care unit (NICU) between June 2015 and December 2023. The neonates were divided into two groups—PAIS and PHS—based on clinical symptoms and cranial imaging findings.ResultsOf the 124 patients, 87 (70.2%) were diagnosed with PAIS, while 37 (29.8%) had PHS. Clonic seizures were observed in 78 cases (62.9%), with apnoea noted in 11 cases (12.6%) within the PAIS group and jaundice in 8 cases (21.6%) within the PHS group. Lesions were primarily located in the left cerebral hemisphere in 53 cases (41.4%), whereas PHS lesions frequently involved the thalamus and basal ganglia (12 cases, 32.4%). Statistical analysis revealed significant differences in risk factors between the PAIS and PHS groups. The PAIS group had a higher rate of conversion from failed trial of labor to cesarean section compared to the PHS group (P = 0.012). Additionally, postnatal thrombocytopenia was more commonly associated with the PHS group than the PAIS group (P = 0.034).ConclusionsOur findings indicate that PAIS is more prevalent within the studied population, with a notable correlation between failed labor trials resulting in cesarean sections and the incidence of PAIS. This suggests a potential link between complications during labor and the occurrence of ischemic strokes. In contrast, postnatal thrombocytopenia was found to be significantly more common in the PHS group, indicating a possible association between low platelet counts and hemorrhagic strokes.